Increasing estrus expression in lactating dairy cows - Sauls, Julie A. (Kansas State University, 2016)
Using an activity monitoring system (AMS) equipped with an accelerometer, 2 experiments were conducted to test the hypotheses that: (1) altering progesterone before inducing luteolysis or (2) exposing cows to estradiol cypionate (ECP) or testosterone propionate (TP) after luteolysis would increase occurrence and intensity of estrus. In experiment 1, cows (n = 154) were fitted with an AMS collar and a pressure-sensitive, rump-mounted device (HW) and assigned to 3 treatments: 1) CL only; 2) no CL + progesterone insert (CIDR); or 3) CL + 2 CIDR to achieve different concentrations of progesterone. Progesterone concentration 24 through 120 h post-treatment was greatest (P < 0.01) in CL + 2 CIDR, followed by CL, and no CL + CIDR cows. Estrus occurred 11 to 12 h earlier (P < 0.01) in no CL + CIDR compared with CL-bearing cows. Estrus intensity was greater (P < 0.05) after CL + 2 CIDR than CL only cows. The AMS and HW determined 68 and 62% of qualifying cows to be in estrus (estrus was defined: follicle ≥ 10 mm at PGF[subscript 2α] and progesterone ≤ 0.5 ng/mL 72 h later), respectively. In experiment 2, cows (n = 203) were equipped with an AMS and a friction-activated, rump-mounted patch (Estrotect patch; ET) and assigned to receive 1 mg ECP, 2 mg TP, or control 24 h after PGF[subscript 2α]. Estradiol 24 h post treatment was greater (P < 0.01) in ECP compared with controls. Estrus expression detected by ET in all cows tended (P = 0.10) to be greater for ECP compared with controls. More (P < 0.05) qualifying cows were detected in estrus after ECP compared with controls. Compared with controls and in response to ECP, estrus occurred 17 to 20 h earlier (P < 0.01) and was of greater (P < 0.05) intensity. The AMS and ET determined 71 and 74% of cows to be in estrus, respectively. Of cows exposed to the AMS, HW, or ET, 62 to 74% were detected in estrus and more than 94% subsequently ovulated. In contrast, of the residual cows not detected in estrus, 60 to 76% ovulated in the absence of detected estrus. Only ECP was successful in inducing more estrus expression and, proportions detected in estrus never exceeded 80%. Given the large proportion of cows ovulating in the absence of estrus, further research is warranted to determine if conception is achievable by inseminating cows not detected in estrus by 80 h post-PGF[subscript 2α].
Keywords: Estrus; Progesterone; Estradiol